2014
DOI: 10.1159/000366104
|View full text |Cite
|
Sign up to set email alerts
|

EEG Theta Power and Coherence to Octave Illusion in First-Episode Paranoid Schizophrenia with Auditory Hallucinations

Abstract: Background: The exact mechanism behind auditory hallucinations in schizophrenia remains unknown. A corollary discharge dysfunction hypothesis has been put forward, but it requires further confirmation. Electroencephalography (EEG) of the Deutsch octave illusion might offer more insight, by demonstrating an abnormal cerebral activation similar to that under auditory hallucinations in schizophrenic patients. Methods: We invited 23 first-episode schizophrenic patients with auditory hallucinations and 23 healthy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…This shows that the Gria1 -knockout-induced increase in local hippocampal peak theta power and peak theta coherence seen in the open field and SNP tests are state-dependent effects (rather than intrinsic changes resulting from GLUA1-ablation) and are determined by the relative novelty/familiarity of the environment. Interestingly, this recapitulates the endophenotype of elevated theta oscillations and theta coherence seen in patients with schizophrenia 8,9,11 , and has also been shown in another mouse model of reduced glutamatergic function ( Sp4 hypomorphs) 50 , which also has an attentional deficit. 51…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This shows that the Gria1 -knockout-induced increase in local hippocampal peak theta power and peak theta coherence seen in the open field and SNP tests are state-dependent effects (rather than intrinsic changes resulting from GLUA1-ablation) and are determined by the relative novelty/familiarity of the environment. Interestingly, this recapitulates the endophenotype of elevated theta oscillations and theta coherence seen in patients with schizophrenia 8,9,11 , and has also been shown in another mouse model of reduced glutamatergic function ( Sp4 hypomorphs) 50 , which also has an attentional deficit. 51…”
Section: Discussionsupporting
confidence: 67%
“…This coherence between the local oscillations in interacting regions might enable the flexible routing of information between them 24 . Abnormalities in long-range coherence have been identified in patients with schizophrenia 59 and may underlie both cognitive and positive symptoms 6,10 . For example, studies in patients with schizophrenia have found abnormally increased baseline theta frequency coherence between multiple brain areas, whereby elevated fronto-temporal theta coherence correlates with positive symptom scores 8,9,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In schizophrenic patients, auditory hallucinations were associated with task-related θ slowing (Zheng et al , 2015) and in cases with a delirium, visual hallucinations were associated with θ-δ slowing (Teeple et al , 2009). Although results of these studies based on other diseases may not be directly comparable with PD, we speculate that these findings suggest a more general cortical desynchronization, rather than network alterations that are specific to PD.…”
Section: Discussionmentioning
confidence: 99%
“…Other findings suggest a positive correlation between increased frequency of hallucinations and low frequency oscillations (i.e., delta and theta; Gattaz et al, 1992;Juszczak, 2011), which might also play a role in the generation of the emotionally charged hallucinations of abusive voices expressing personal insults (Nayani & David, 1996). More specifically, recent research has demonstrated the link between fronto-central theta power abnormalities and sensory processing deficits (Roa Romero et al, 2016), also proposing a role for fronto-temporal delta connectivity (Ford et al, 2002) and frontal/central/temporal theta power/coherence dysfunctions in patients with paranoid schizophrenia experiencing auditory hallucinations (Zheng et al, 2015). Furthermore, lower theta power in the hippocampus has been shown to precede AVH (Van Lutterveld et al, 2012).…”
Section: Introductionmentioning
confidence: 99%